Vehicle-Driver Behavioural-Responses Defined by Radio-Navigation System GPS - Čop, Rudi; Dimc, Franc (Promet - Traffic&Transportation, 2004)
From the very beginning of its usage the navigation systemGPS has been applied in studying the cases of the car followingbehaviour of two-vehicle platoons. The navigation receiver isused for vehicle position and speed data collections. The measurementaccuracy is to be improved by the real-time dGPScorrection-data or by additional data post-processing. For additionalmeasurement of the vehicle-to-vehicle separation, bothvehicles should be equipped with a GPS receiver. The vehicle-to-vehicle separation is calculated later on, during the datapost-processing.This paper describes the choice of the experimental setup,on the basis of the radio-navigation system GPS, which may beused for recording the data on location, speed and time. Thepresented measurement results have been attained in two steps:first, the data were collected, through the process of tracking oftwo-vehicle platoons in real life traffic-flow, and then processed.The selected mathematical model is based on the PIDcontroller in the closed-loop control system. It enables evaluationof the measurement results and assessment of the behaviouralelements of each driver.